Knockout of G protein β5 impairs brain development and causes multiple neurologic abnormalities in mice - Jian‐Hua Zhang; Mritunjay Pandey; E M Seigneur; Leelamma M. Panicker; Lily Y. Koo; Owen Schwartz; Weiping Chen; Ching‐Kang Chen; William F. Simonds (2011)
J. Neurochem. (2011) 119 , 544–554. Abstract Gβ5 is a divergent member of the signal‐transducing G protein β subunit family encoded by GNB5 and expressed principally in brain and neuronal tissue. Among heterotrimeric Gβ isoforms, Gβ5 is unique in its ability to heterodimerize with members of the R7 subfamily of the regulator of G protein signaling proteins that contain G protein‐γ like domains. Previous studies employing Gnb5 knockout (KO) mice have shown that Gβ5 is an essential stabilizer of such regulator of G protein signaling proteins and regulates the deactivation of retinal phototransduction and the proper functioning of retinal bipolar cells. However, little is known of the function of Gβ5 in the brain outside the visual system. We show here that mice lacking Gβ5 have a markedly abnormal neurologic phenotype that includes impaired development, tiptoe‐walking, motor learning and coordination deficiencies, and hyperactivity. We further show that Gβ5‐deficient mice have abnormalities of neuronal development in cerebellum and hippocampus. We find that the expression of both mRNA and protein from multiple neuronal genes is dysregulated in Gnb5 KO mice. Taken together with previous observations from Gnb5 KO mice, our findings suggest a model in which Gβ5 regulates dendritic arborization and/or synapse formation during development, in part by effects on gene expression.